BPI science awardees 2002 - De La Salle University, Manila (Animo Repository, 2002)
The University Honors and Awards Committee cited Lasallian students Karen Joy Nomorosa, BS in Computer Science major in Computer Engineering Jose Eduardo Ang, BS in Mathematics with specialization in Actuarial Science/Statistics and Nicklaus Erick Sy, BS in Chemical Engineering and a pioneer Star scholar as BPI Science Awardees 2002.